1989
DOI: 10.3171/jns.1989.70.6.0841
|View full text |Cite
|
Sign up to set email alerts
|

Outcome following aneurysm wrapping: a 10-year follow-up review of clipped and wrapped aneurysms

Abstract: One hundred and eighty-one patients with single aneurysms involving the anterior circulation were treated either by wrapping (60 cases) or clipping (121 cases), and 96.1% of them were followed for 10 years. The rate of early rebleeding (less than 6 months) from wrapped aneurysms was 8.6% (confidence interval 1.4% to 15.8%) and the late rebleeding (6 months to 10 years) rate was 1.5% per annum (confidence interval 0.3% to 2.5%/yr). Wrapping an aneurysm offers some protection from rebleeding, particularly during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0
4

Year Published

1995
1995
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(37 citation statements)
references
References 16 publications
0
33
0
4
Order By: Relevance
“…After the introduction of microsurgical technology, these studies showed that the rebleeding rate of wrapped aneurysms was generally low 4,16,17) , but these studies suggested that the wrapping technique was still less effective than clipping in preventing early rebleeding. Todd et al 17) reported that their early rebleeding rate (within the first 6 months) was 8.6%, and their late rate of rebleeding was 1.5% per year. Another study using biobond and histoacryl with gauze showed that the total rebleeding rate was about 10.5% (4/38) 2) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…After the introduction of microsurgical technology, these studies showed that the rebleeding rate of wrapped aneurysms was generally low 4,16,17) , but these studies suggested that the wrapping technique was still less effective than clipping in preventing early rebleeding. Todd et al 17) reported that their early rebleeding rate (within the first 6 months) was 8.6%, and their late rate of rebleeding was 1.5% per year. Another study using biobond and histoacryl with gauze showed that the total rebleeding rate was about 10.5% (4/38) 2) .…”
Section: Discussionmentioning
confidence: 99%
“…Our wrap-and-clip technique or clip reinforcement wrapping technique using temporalis can be a favored method in unclippable aneurysm cases. In earlier studies, there was a degeneration and resorption of the wrapped temporlis muscle, and resulted in late rebleeding 2,17) . However, such cases have not been found in our hospital yet.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…31) The wrapping procedure is safe and durable, so can prevent aneurysmal growth or hemorrhage. However, wrapping has a re-rupture rate of 12-18%, 2,4,6,13,21,22,30) indicating insufficient safety and durability to prevent re-rupture and re-growth after treatment. Incomplete wrapping has resulted in many cases of re-rupture.…”
Section: Discussionmentioning
confidence: 99%